A diagnostic dashboard to evaluate country water security - Doeffinger, T.; Borgomeo, Edoardo; Young, W. J.; Sadoff, Claudia W.; Hall, J. W. (IWA Publishing, 2020)
While water security is widely regarded as an issue of global significance and concern, there is not yet a consensus on a methodology for evaluating it. The difficulty in operationalizing the concept comes from its various interpretations and characteristics at different spatial and temporal scales. In this paper, we generate a dashboard comprised of 52 indicators to facilitate a rapid assessment of a country’s water security and to focus the first step of a more comprehensive water security diagnostic assessment. We design the dashboard around a conceptualization of water security that builds upon existing framings and metrics. To illustrate its usefulness, we apply the dashboard to a case study of Pakistan and a regional cross-country comparative analysis. The dashboard provides a rapid view of the water security status, trends, strengths, and challenges for Pakistan. The cross-country comparative analysis tentatively identifies relationships between indicators such as water stress and the transboundary dependency ratio, with countries exhibiting high values in both variables being especially vulnerable to transboundary water risk. Overall, this dashboard (1) provides quantitative information on key water-related variables at the country level in a consistent manner and (2) helps to design and focus more in-depth water security diagnostic studies.